Experiences of simulated patients in clinical skills laboratory: A qualitative study - Shange-Goba, Mbalenhle P.; Willemse, Juliana J. (Curationis (Pretoria), 2025)
Background Nursing simulations with simulated patients (SPs) have proven effective in creating realistic opportunities to enhance the students’ clinical competence within a safe learning environment. This setting helps to reduce anxiety and increases self-confidence among health sciences students. This study aimed to explore experiences of SPs in clinical skills laboratory of a Department of Nursing at a university in Western Cape. Objectives Objectives were set to explore the contextual elements of SPs’ experiences during clinical skills sessions, identify educational design aspects from those experiences and assess their views on student outcomes. Method A qualitative descriptive, exploratory and contextual design was used. Data were collected through semi-structured interviews with eight SPs. The data were coded to develop emerging themes and sub-themes, following Braun and Clark’s systematic analysis process. An independent coder reviewed findings, and themes were confirmed during a consensus meeting. Results This study found that SPs engaged in multiple role-play consultations, improving their understanding of healthcare consultation structures and rules. They recognised their roles in achieving the outcomes needed for students. Conclusion This study confirmed existing literature on SPs in a clinical skills laboratory within a Department of Nursing. Participant interviews provided verbatim quotations that enriched findings. Contribution The study aimed to recommend ways for a Department of Nursing to support SPs in improving their laboratory skills and enhancing student learning. Expanding this research to other nursing education institutions could provide a broader understanding of SPs’ experiences.